2016
DOI: 10.1371/journal.pone.0167733
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Articular Cartilage Thickness Reduction on Meniscus Biomechanics

Abstract: ObjectiveEvaluation of the biomechanical interaction between meniscus and cartilage in medial compartment knee osteoarthritis.MethodsThe finite element method was used to simulate knee joint contact mechanics. Three knee models were created on the basis of knee geometry from the Open Knee project. We reduced the thickness of medial cartilages in the intact knee model by approximately 50% to obtain a medial knee osteoarthritis (OA) model. Two variants of medial knee OA model with congruent and incongruent conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
2
9
0
1
Order By: Relevance
“… Arno et al (2012) suggested that the meniscus is not able to reduce forces and pressures acting between the articular cartilage and prevent degeneration in medial knee OA. In our previous study ( Łuczkiewicz et al, 2016 ) we showed that the reduction in the role of the meniscus in the transmission of static load in the medial compartment may be attributed to incongruence between contact surfaces resulting from a 50% reduction in cartilage thickness. Here, the decrease in force between the tibial cartilage and the medial meniscus in model M ( Table 5 ) showed that the medial meniscus did not take a greater load in the OA model due to the reduction in its compressive stiffness.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… Arno et al (2012) suggested that the meniscus is not able to reduce forces and pressures acting between the articular cartilage and prevent degeneration in medial knee OA. In our previous study ( Łuczkiewicz et al, 2016 ) we showed that the reduction in the role of the meniscus in the transmission of static load in the medial compartment may be attributed to incongruence between contact surfaces resulting from a 50% reduction in cartilage thickness. Here, the decrease in force between the tibial cartilage and the medial meniscus in model M ( Table 5 ) showed that the medial meniscus did not take a greater load in the OA model due to the reduction in its compressive stiffness.…”
Section: Discussionmentioning
confidence: 91%
“…The finite element method (FEM) serves as a useful tool for investigating the mechanical status of the knee joint in different pathological conditions ( Kluess et al, 2009 ; Łuczkiewicz et al, 2016 ). Previous works ( Peña et al, 2005 ; Zielinska & Haut Donahue, 2006 ; Mononen, Jurvelin & Korhonen, 2013 ; Shriram et al, 2019 ; Zhang et al, 2019 ; Li et al, 2020 ) have focused on the influence of degenerative meniscal tears and meniscectomies on knee biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…The material properties were assigned according to pertinent literature. Several studies 4854,57 have assumed the femur and tibia as rigid bodies because of their relatively high density and Young’s modulus compared to the cartilage and menisci in the knee joint. On the other hand, previous FEA studies 56,5862 did not take into account the difference between cancellous and cortical bone and considered the whole bony structure of the knee joint as cortical bone.…”
Section: Methodsmentioning
confidence: 99%
“…los ligamentos articulares) (Orozco et al, 2018) y los tejidos conectivos especializados cartilaginosos (ej. los discos articulares) (Luczkiewicz et al, 2016). Durante el proceso de elaboración del MEF se debe construir la geometría del material a estudiar, utilizando un software que funciona como una herramienta de simulación de casos hipotéticos de carga para la predicción de posibles condiciones clínicas, tales como la osteoartrosis (Klets et al, 2018).…”
Section: Introductionunclassified